The Bairn’s Blain- Fibromatosis Colli - Anubha, Bajaj (Journal of Clinical and Diagnostic Pathology, 2020)
Preface Fibromatosis colli is an exceptional, benign neoplasm of infancy constituted by spindle-shaped cells of sternocleidomastoid muscle. Fibromatosis colli emerges within specific sites such as distal or inferior segment of sternocleidomastoid muscle and is accompanied by diffuse enlargement of the muscle. Although nomenclated as “sternocleidomastoid tumour” or “sternocleidomastoid pseudo-tumour of infancy”, the designation is a misnomer, as the condition is non neoplastic although it may be denominated as a congenital fibrotic disorder.
Keywords: Circumstance- Parachordoma